Study the Effect of Seasonal Influenza Virus Infection on Patients with Acute Myocardial Infarction and Acute Kidney Injury. - Saleem, Maysoon Mohammad Najeeb Mohammad (Al-Nahrain Journal of Science, 2016)
Influenza is a highly contagious acute respiratory disease of global importance that has caused epidemics and pandemics of human disease for centuries [1]. This study was designed to evaluate the effect of seasonal influenza virus infection on heart and kidney diseases. To investigate the effect of seasonal influenza virus infectionon acute myocardial infarction and acute kidney injury. The study enrolled a total of 178 subjects, involved 150 patients with influenza virus infection and with heart and kidney diseases, they were consisted of two group, the first investigated group was 101 patients with influenza and acute myocardial infarction (AMI), consisted of G1 of 41 patients suffering from acute myocardial infarction, G2 involved 32 patients infected with influenza and G3 were formed of 28 patients of acute myocardial infarction with influenza, they were compared with 14 normal healthy individual. The second group consisted of 49 patients with acute kidney injury AKI, G1 involved 10 patients suffering from acute kidney injury AKI, G2 were 19 patients suffering from mixed influenza virus infection according to physician reports, and G3 were 20 patients of influenza with acute kidney injury AKI they were compared with 14 normal healthy subjects. Patients with influenza and AMI were investigated for the activities of enzymes lactate dehydrogenase LDH and creatine kinase CK. Patients with influenza and AKI were evaluated for urea, uric acid, creatinine, total protein, albumin, globulin, and enzymes activities of amylase, gammaglutamyl transferase (GGT) and (CK) and LDH. They were compared with normal healthy individual. All the specimens of patients with influenza were obtained from different laboratories hospitals in Baghdad. Statistical analysis shows that there was very highly significant increase for enzymes activities LDH and CK activities (P ˂ 0.001) for patients of G1 acute myocardial infarction, G2 influenza and, G3 influenza with AMI in comparison with normal healthy. The result for patients of G1 with acute kidney injury AKI show very highly significant increase in the enzymes activities of amylase, gammaglutamyl transferase, creatine kinase, and lactate dehydrogenase (P ˂ 0.001) and in the concentration of urea, creatinine and uric acid ,and very highly significant decrease in total protein, albumin, and globulin (P ˂ 0.001) as compared with normal healthy individual. Patient of G2 suffering from influenza disease show very highly significant increase in the enzyme s activities of CK, LDH, and albumin (P ˂ 0.001).Highly significant change in protein, urea, creatinine and uric acid in comparing with normal healthy. Infection of influenza virus is one of the leading causes of morbidity and mortality in patients with heart and kidney diseases than in normal healthy persons. This may be because of inherently altered activity of the immune system. In our cohort of patients with influenza virus infection, patients who are suffering from influenza must be investigated for heart disease acute myocardial infarction ,acute kidney diseases, people with chronic medical disorders such as cardiovascular disease are particularly at risk.